2022
DOI: 10.2147/nss.s345328
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Attentional Vulnerability to Sleep Deprivation: A Multivariate Pattern Analysis of DTI Data

Abstract: Background Large individual differences exist in sleep deprivation (SD) induced sustained attention deterioration. Several brain imaging studies have suggested that the activities within frontal-parietal network, cortico-thalamic connections, and inter-hemispheric connectivity might underlie the neural correlates of vulnerability/resistance to SD. However, those traditional approaches are based on average estimates of differences at the group level. Currently, a neuroimaging marker that can reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 58 publications
2
8
0
Order By: Relevance
“…Widespread connection differences were found in several large white matter structures and short‐range connections including the brain cortex and the basal ganglia, cingulate, and thalamus regions. Our findings were consistent with emerging evidence of structural network abnormalities in SD‐vulnerable individuals, especially for the white matter connections within the frontal–parietal attention network, and the thalamus to prefrontal cortex 9,42,43 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Widespread connection differences were found in several large white matter structures and short‐range connections including the brain cortex and the basal ganglia, cingulate, and thalamus regions. Our findings were consistent with emerging evidence of structural network abnormalities in SD‐vulnerable individuals, especially for the white matter connections within the frontal–parietal attention network, and the thalamus to prefrontal cortex 9,42,43 …”
Section: Discussionsupporting
confidence: 90%
“…Our findings were consistent with emerging evidence of structural network abnormalities in SD-vulnerable individuals, especially for the white matter connections within the frontal-parietal attention network, and the thalamus to prefrontal cortex. 9,42,43 Similar hub distributions were found in both groups. However, hubs in the right orbital superior frontal gyrus and cuneus were only found in the resistant group.…”
Section: F I G U R Esupporting
confidence: 75%
“…Diffusion magnetic resonance imaging (dMRI) is a non-invasive approach that measures the diffusion of water molecules in tissue, providing information about the underlying brain microstructure ( Pierpaoli et al, 1996 ). In recent years, many studies have used dMRI to investigate the effect of SD on brain microstructure ( Rocklage et al, 2009 ; Cui et al, 2015 ; Elvsashagen et al, 2015 ; Zhu et al, 2017 ; Voldsbekk et al, 2021 ; Wang et al, 2022 ). For instance, one diffusion tensor imaging (DTI) study found that SD was associated with impaired white matter (WM) integrity [as reflected by reduced fractional anisotropy (FA)] of the bilateral frontotemporal and parieto-occipital tracts, corpus callosum, thalamus, and brain stem ( Elvsashagen et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, one diffusion tensor imaging (DTI) study found that SD was associated with impaired white matter (WM) integrity [as reflected by reduced fractional anisotropy (FA)] of the bilateral frontotemporal and parieto-occipital tracts, corpus callosum, thalamus, and brain stem ( Elvsashagen et al, 2015 ). In addition, several DTI studies have reported that WM microstructural properties enable the prediction of cognitive vulnerability to SD ( Rocklage et al, 2009 ; Wang et al, 2022 ). Moreover, the individual’s cognitive stability/resistance to SD is associated with the integrity of the WM tract, which connects the frontoparietal attention networks ( Cui et al, 2015 ; Zhu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation